2021
DOI: 10.5435/jaaos-d-20-00810
|View full text |Cite
|
Sign up to set email alerts
|

American Academy of Orthopaedic Surgeons Appropriate Use Criteria: Early Screening for Psychosocial Risk and Protective Factors

Abstract: The Major Extremity Trauma and Rehabilitation Consortium and the American Academy of Orthopaedic Surgeons (AAOS) have developed Appropriate Use Criteria for the Early Screening for Psychosocial Risk and Protective Factors. Evidence and clinical expertise were used to develop criteria for addressing mental and social health opportunities to help people recover from musculoskeletal injuries to the extremity, spine, and pelvis. The criteria were developed by identifying observable symptoms and results of screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Notably, 86% of potential screening interventions were rated as "appropriate," 14% were rated as "may be appropriate," and 0% were rated as "rarely appropriate" 31 . This indicates that experts in multiple medical fields recommend that orthopaedic surgeons always evaluate and screen for mental and social health 31 .…”
Section: Preoperative Screening and Patient Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, 86% of potential screening interventions were rated as "appropriate," 14% were rated as "may be appropriate," and 0% were rated as "rarely appropriate" 31 . This indicates that experts in multiple medical fields recommend that orthopaedic surgeons always evaluate and screen for mental and social health 31 .…”
Section: Preoperative Screening and Patient Optimizationmentioning
confidence: 99%
“…*DSM-5 = Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, and PTSD = posttraumatic stress disorder.†Excerpt from Piuzzi and Ring 31 .…”
Section: Preoperative Screening and Patient Optimizationmentioning
confidence: 99%
“…Musculoskeletal injury can affect mental and social health depending on the severity of symptoms and the magnitude of self-reported activity limitations. 22) Patients can experience both stress and distress, as well as unhelpful cognitive bias about pain, such as fear of painful movement during recovery. They can experience sadness, anger, guilt, shock, and denial.…”
Section: Mental Disorders In Trauma Patientsmentioning
confidence: 99%
“…The American Academy of Orthopedic Surgeons reported that psychiatric problems, such as anxiety, depression, and posttraumatic stress disorder (PTSD), can affect clinical outcomes and should be evaluated after trauma. 22) …”
Section: Mental Disorders In Trauma Patientsmentioning
confidence: 99%
See 1 more Smart Citation